A nulle immersion: Klimt in Paris (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
In 1940 Luciano Emmer (who was born 100 years ago, in 1918) began his career as a filmmaker by making a series of art documentaries on art. In particular, one of the documentaries which gave rise to many objections and discussions was Racconto di un affresco (Tale of a fresco) on Giotto’s fresco cycle in the Scrovegni Chapel in Padua. The first version was made in 1938, a second one in 1946 . Emmer took the liberty of ‘moving’ the angels around the cross of Christ using the same images of Giotto through the technique of one‒step animation. He inserted movement, the explicit passage of time in an untouchable work of art. He then repeated the same operation with some of the drawings by Leonardo da Vinci and with this documentary he won the Leone d’Oro at the Festival del Cinema di Venezia (Venice Film Festival) in 1954. Since then many years have passed and documentaries on artists and their works have become very popular. The works are analysed in detail, the camera enters inside the artwork, the picture and the painting becomes three‒dimensional, and the actions that take place become animated. Even art shows are changing, the audience should be amused, must be able to play in a kind of perennial video games with the works of artists. It was natural enough that this would lead to a new kind of exhibition that probably will not be called exhibition anymore but ‘experience’, whatever the meaning of this word.